What is hidden behind the gender differences of carotid atherosclerosis? - Oleg V. Gaisenok (Russian Open Medical Journal)
This review article reveals possible causes that may underlie gender differences of carotid atherosclerosis: vascular anatomy, localization and morphology of atherosclerotic plaques, different effects and prevalence of known risk factors between genders (arterial hypertension, hypercholesterolemia, obesity, smoking, alcohol consumption, depression / stress). A separate place in the review is given to markers of inflammation and the protective effect of female sex hormones.